As mulheres na expansão material de Fortaleza nos anos de 1920 e 1930 - Viana Júnior, Mário Martins (2009)
In this work I tried to comprehend the process of material expansion in Fortaleza City on the decades of 1920 and 1930 and its involvement in the gender relationships. To do that, I’ve focused in the actions of women who were inserted by themselves and made that process happens. This group is composed by liberal professionals, proprietary traders, and also by poor employees and domestic workers, among some others. So, I’ve tried to show some of many ways that how this expansion used to touch different subjects, resulting in one hand, some approximations and solidarity relationships, but in the other, conflicts and contradictions expressed in gender aspects. I’ve used many kind of documents as features, like crime processes, books of police registers, commercial scriptures, newspapers, city guides and almanacs, legislative codes and chronicles.